Reading habit among students: a case study in Universiti Teknikal Malaysia Melaka (UTEM) / Nursyella Mohamad Nazri and Ahmad Wafil Razali - Mohamad Nazri, Nursyella; Razali, Ahmad Wafil (Faculty of Administrative Science and Policy Studies, 2012)
The aim of this quantitative research is to identify the reading habit among students from the Universiti Teknikal Malaysia Melaka (UTEM). There are four variables were used in this research to collect quantitative data from the subjects which were the Function of Library, Parents Influence, Peers Influence, and Book Availability. The respondents for this study consist of the students of Universiti Teknikal Malaysia Melaka City Campus. The data from this research was collected by the questionnaire that given to the respondents. 357 questionnaires had been design and distributed among the students to indicate whether there is a relationship between the variables and reading habits. Then the data were analyzing using reliability analysis, frequency analysis, Pearson’s correlation coefficient, and multiple linear regressions. Result of the study show that there are significance positive relationship between the four variables and reading habit. The result also indicate that the Function of Library was found to be the only independent variable with most significant impact on reading habit among the teenagers in UTEM (b=2.057, p<.001). The findings imply that the good libraries function will provide quality sources, services, and unite a large cross-section of people through the effectiveness of their design and the quality of their services and collections.